2009
DOI: 10.1177/000348940911800104
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Oral Tongue Cancer in a 22-Year-Old Pregnant Woman

Abstract: Management of advanced oral carcinoma in pregnancy presents a unique set of challenges. Few studies have described chemotherapy and radiotherapy during pregnancy, and long-term results are needed. Care must be taken to balance appropriate and adequate treatment of disease and to ensure the safety of the patient and the fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…We identified thirty two cases of pregnant patients with tongue SCC following a literature search as shown in table 1, with the current patient included. 4,5,6,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26 We excluded cases reported as a regional recurrence of tongue SCC during pregnancy. Only one pregnant patient with SCC of the tongue in the published literature chose termination of pregnancy prior to treatment of the malignancy; however, publication bias must be considered when interpreting this.…”
Section: Discussionmentioning
confidence: 99%
“…We identified thirty two cases of pregnant patients with tongue SCC following a literature search as shown in table 1, with the current patient included. 4,5,6,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26 We excluded cases reported as a regional recurrence of tongue SCC during pregnancy. Only one pregnant patient with SCC of the tongue in the published literature chose termination of pregnancy prior to treatment of the malignancy; however, publication bias must be considered when interpreting this.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathogenesis of oral cavity cancer in young female patients could be different from those occurring in older patients (3,5). Pregnancy has been shown to be associated with OSCC but there is a paucity of data regarding this etiology as these studies are primarily case reports discussing the challenges that clinicians face in administering treatment that is of maximal benefit to the patient and minimal risk to the fetus (4,6-10). …”
Section: Introductionmentioning
confidence: 99%
“…2 Historically, scientific literature has demonstrated a preferential incidence of oral cancers in men aged 50 to 70 years. [2][3][4][5][6][7] However, recent epidemiological studies have shown an increase in the development of OSCC in patients under 45 years old. 8,9 In those cases, tumour behaviour is different and patients have a poor prognosis in comparison to cancer in older adults.…”
Section: Case Reportmentioning
confidence: 99%